РОЗМЕЖУВАННЯ ТА ВЗАЄМОДІЯ ФІНАНСОВОГО ПРАВА Й АДМІНІСТРАТИВНОГО ПРАВА - Очкуренко, Сергій Володимирович (SUPREMANCE OF LAW, 2017)
The article is devoted to substantiating the delineation of certain spheres of financial and administrative regulations, as well as to identify areas of the closest interaction of these legal branches. The article clarifies the content of distinctive features and characteristics of financial law. These features are used by the author to determine the branch belonging to specific legal relations and the delineation of financial law and administrative law subjects. A special attention is drawn to the areas of the closest interaction of these legal branches.